2023
DOI: 10.1007/s11426-023-1560-0
|View full text |Cite
|
Sign up to set email alerts
|

Construction of chiral through-space luminophores via symmetry breaking triggered by sequenced chlorination

Abstract: The construction of molecular chirality is crucial for exploring novel luminophores with chiroptical properties. Classic asymmetric synthesis of chiral center or axial is not powerful enough on throughspace architecture. Accessible methodologies for breaking molecular symmetry could be promising but remain less investigated. Herein, we report a novel methodology for constructing chiral through-space luminophores via simple chlorination on bridged carbazole motifs. The chlorination breaks the molecular symmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Planar chirality, compared to axial and point chirality, has sig-nificant practical implications for the construction of intrinsic CP-RTP materials but is challenging. 32 Zuo et al recently reported a series of chiral molecules based on the [2.2]paracyclophane unit, which exhibits prominent RTP upon aggregation and excellent CPL in solution through asymmetric substitution on the chiral center (as shown in Scheme 4a). 33 Helicenes display pronounced conformational asymmetry attributed to their inherent planar chirality.…”
Section: Cp-rtp Systems Based On Planar Chirality and Othersmentioning
confidence: 99%
“…Planar chirality, compared to axial and point chirality, has sig-nificant practical implications for the construction of intrinsic CP-RTP materials but is challenging. 32 Zuo et al recently reported a series of chiral molecules based on the [2.2]paracyclophane unit, which exhibits prominent RTP upon aggregation and excellent CPL in solution through asymmetric substitution on the chiral center (as shown in Scheme 4a). 33 Helicenes display pronounced conformational asymmetry attributed to their inherent planar chirality.…”
Section: Cp-rtp Systems Based On Planar Chirality and Othersmentioning
confidence: 99%